COMPARATIVE TREND ANALYSIS IN COST OF PADDY CULTIVATION AND PROFITABILITY ACROSS THREE STATES OF INDIA - Chandra Guptha; Prabhakaran T. Raghu; N Aditi; N.N. Kalaiselvan; Arivudai Nambi V (European Scientific Journal, ESJ, 2014)
Agriculture has seen tremendous changes in the past century, with agricultural research investments paving the way for productivity gains leading to reduction in production costs and capacity to carter larger population. The contribution of agriculture to the GDP is on the decline and so does profitability. Farmer suicides were not a common phenomenon in India before 1990, but more than two lakh farmers committed suicides between 1990 and 2010. The underlying causes for failure in agriculture could be many including climate change, reduction in profitability and fragmentation of land. This article explores the trends in the cost of cultivation of paddy and its profitability in three Indian states of Kerala, Odisha and Tamil Nadu during the period 1999-2011. It is observed that the factors like hired machine and human labor, fertilizer, are all growing in varying proportions leading to an increase in the cost of cultivation. In the years showing profits, Profitability seemed to be averaging around ten percent and while in most of the years loss was reported. Over the years, the increase in cost of cultivation seems to be stable in contrast with the increase in value of paddy produced by farmers. The APM project has appropriately addressed issues of increasing cost of manures through introduction of vermicomposting. Other appropriate techniques and technologies have also been demonstrated for increased profitability. Efforts need to be taken to create an enabling environment to ensure a commensurate income to farmers for a dignified life.